A Tandem [3+2] Cycloaddition–Elimination Cascade Reaction to Generate Pyrrolo-[3,4-c]pyrrole-1,3-diones - Martinez-Ariza, Guillermo; Dietrich, Justin; De Moliner, Fabio; Hulme, Christopher (Synlett, 2013)
An efficient tandem [3+2] cycloaddition–elimination cascade sequence has been developed enabling assembly of the pharmacologically relevant pyrrolo-[3,4-c]pyrrole-1,3-dione chemotype. The strategy involves simple mixing of readily accessible oxazolin-2-ones and pyrrole-2,5-diones in the presence of base under mild conditions, rendering the title compounds in typically excellent yields. Of note, this route allows for installation of three points of diversity and is ideal for combinatorial applications and parallel synthesis production campaigns.
Keywords: cycloaddition; elimination; tandem reaction; bicyclic compounds; ylides